The Effect of Balance and Combined Exercises on Pain and Functional Characteristics of Female Athletes With Chronic Ankle Instability - Fatemeh Haataamee; Seyed Sadrodin Shojaodin (Biyumikānīk-i varzishī)
Objective: The aim of this study was to compare the effects of balance exercises and combined exercises (neuromuscular and stabilization exercises) on pain, function, and range of motion of female athletes with chronic ankle instability. Methods: Participants were 30 female athletes with chronic ankle instability selected using a convenience sampling technique and randomly assigned into three groups balance exercises (n=10), combined exercises (n=10) and control (n=10). The amount of pain was measured by the Visual Analog Scale (VAS). Functional characteristics were tested by side hop test, 8 hop test, single-leg triple hop test, and single-leg hop test. A goniometer was used to measure ankle dorsiflexion and plantar flexion range of motion. Both exercise groups performed their exercises for 6 weeks (3 sessions per week each for 60 minutes). After the intervention, they went under post-test assessment and their results were then compared. The Levene's test was used to test the homogeneity of variances in the pre-test phase, while Analysis of Covariance (ANCOVA) was used to examine the between-group changes, Tukey's post hoc test for determining the location of the difference between groups, and t-test for assessing the differences within groups. Results: Balance and combined exercises had a significant effect on the subjects 'pain (P=0.03 and 0.01), functional characteristics (P≤0.01) and ankle dorsiflexion (P=0.01) and plantar flexion (P=0.01 and 0.02) range of motion. Comparing two exercise programs, it was found that the effect of combined exercises on pain, function and dorsiflexion range of motion of subjects was higher. Conclusion: It is recommended that for correct and timely rehabilitation of the athletes with ankle injury, balance exercises along with combined exercises should be used to reduce their pain, and improve function and range of motion.